Water and fire : the myth of the flood in Anglo-Saxon England (Manchester : Manchester University Press, 2006)
"The story of Noah's Flood is one of the Bible's most popular stories, and flood myths are preserved by cultures across the world. This book presents the first comprehensive study of the incorporation of the Flood myth into the Anglo-Saxon imagination, ranging from the works of Bede to Beowulf. Focusing on literary representations, this original study contributes to the understanding of the Anglo-Saxons' perception of their place in a universal history unfolding in the interval between the primeval deluge and a future - perhaps imminent - flood of fire, which would destroy the world. This book examines in detail a diverse range of texts which focus on the myth of the Flood, revealing both an imaginative diversity and shared tradition in the interpretation of the myth. On the one hand, the Anglo-Saxons saw in the Flood a climactic event in God's ongoing war with his more rebellious creatures, especially the foolish giants, while on the other they saw in allegory the mystery of redemption through baptism. Most striking of all is their invention of Noah's fourth son, born in the ark, from whom they claimed special descent. The author carefully studies a range of texts against their historical background, and discusses shifting emphases in the way the Flood was interpreted for Anglo-Saxon audiences. The book concludes with a discussion of Beowulf, where the Flood myth constitutes a sustained metaphor across the poem, and the relationship is explored between its presentation of the myth and that found in other Anglo-Saxon texts."--Jacket
Introduction. Myth ; The Bible and myth ; The classical tradition ; Early Germanic tradition ; Replacing myths -- 'You see the water, you see the wood' : the Bible and the fathers. The Old Testament ; The New Testament ; Patristic interpretation -- A manifold mystery : Bede on the Flood. Audience ; Bede and the Flood ; Ark and Church ; Flood and baptism ; The Flood in history ; Flood and apocalypse ; Noah and Christ ; Noah the preacher ; The Flood and the foolish giants -- Learning the lesson of the Flood. Niall and Noah ; The Annals of St-Bertin ; Alcuin and the Vikings ; Alfred and the Flood ; Ælfric and the Flood ; Before the Flood : Noah and his generation ; The Flood in history ; The Church in the world ; Translation and commentary ; Eschatology -- Flood, covenant and apocalypse in Old English poetry. Genesis A ; Exodus ; Andreas ; The flooding of the city -- Planting Noah's seed. The genealogies ; Sceaf and Wessex ; Reactions -- Beowulf and the myth of the Flood. Creation to Flood ; Ancient work of giants ; Grendel's mere ; Grendel and the underworld ; Wulf's field ; The dragon ; Beowulf's death ; Beowulf and Andreas.
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, viewed June 8, 2018).
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
eBooks on EBSCOhost
Keywords: Christian literature, English (Old) -- History and criticism; Deluge in literature; Christianity and literature -- England -- History -- To 1500.; English literature -- Old English, ca. 450-1100 -- History and criticism; Mythology, Anglo-Saxon.; Floods -- Mythology -- England; Floods in literature; Littérature chrétienne anglaise (vieil anglais) -- Histoire et critique; Déluge dans la littérature.; Littérature anglaise -- ca 450-1100 (Vieil anglais) -- Histoire et critique; Mythologie anglo-saxonne.; Inondations -- Mythologie -- Angleterre; Inondations dans la littérature.; BODY, MIND & SPIRIT -- Gaia & Earth Energies; RELIGION -- Christianity -- General; Christian literature, English (Old); Christianity and literature; Deluge in literature; English literature -- Old English; Floods in literature; Mythology, Anglo-Saxon; England; 18.05 English literature; Literatur; Sintflut; Altenglisch; Old English; Zondvloed; Altenglisch; To 1500; Criticism, interpretation, etc; History